Effect of antineoplastic agents on non proliferating yeast cells: a possible membrane effect of doxorubicin. - Karavokyros, I; Delitheos, A (Anticancer Res, 1997)
The effect of antineoplastic agents on non proliferating cells of Saccharomyces cerevisiae was investigated. Non growing populations were obtained by suspending cells in saline or H2O and survival rates were determined after exposing the cells to various commercially available agents for five hours. The only agent found to be effective was Doxorubicin which reduced survival rates to less than 5% (p < 0.001). The action of this drug could be detected in only 4 minutes and was not concentration dependent, therefore it is probable that DNA damage is caused mostly by oxygen free drug radicals. Furthermore, our observations strongly imply the damage of cellular membranes is an alternative reason for cell death, with phosphatidyl-inositol being the most probable candidate target for the drug.
Keywords: Antibiotics, Antineoplastic; Cell Membrane; Doxorubicin; Saccharomyces cerevisiae